Upaya Kanada untuk Menarik Minat Imigran menjadi Permanent Residence melalui Jaminan yang “Memanjakan”: Indonesia - Kinanti, Shafa Diva (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2023)
The phenomenon of international migration is influenced by many factors, one of which is the need for labor. Labor is an important element in economic activities because labor plays a role in the stages of production and industry. For a large country like Canada, labor is very important as a maintainer of the quality and quantity of its workforce. However, maintaining a stable workforce is difficult due to problems related to wages and the workforce. Therefore, concrete policies and steps are needed as a prevention or solution to the decline in the number of workers in Canada. And one of them is through international migration. By using a qualitative descriptive method, this study will briefly explain the problems raised through a neoclassical economic perspective as the author's point of view. Keywords: Canada, Industry, Labor, Migration, Wages